Uma abordagem integrada da economia evolucionista e da nova economia institucional para entendimento da relação universidade-empresa : o caso NEXEM/UFES - Sessa, Celso Bissoli (2009)
Considering the growing importance of scientific knowledge for technological progress of companies, there is an important role played by universities. In this paper, the importance of the relationship between innovations and institutions in the interaction between universities and firms are analyzed through the framework of Evolutionary Economics and New Institutional Economics. The main models of university-industry interaction and its impact on scientific and technological policies in Brazil are presented, further an analysis of the Law of Innovation. The interaction between universities and companies in Brazil are analyzed using information from the directory of groups of CNPq and from the IBGE`s Industrial Research of Technological Innovation (Pintec). For empirical evidence of the study, are analyzed the Núcleo de Excelência em Estruturas Metálicas e Mistas (NEXEM), the result of partnership between the Federal University of Espirito Santo (UFES) and Companhia Siderurgica de Tubarão (CST).